The social impact of oral and facial pain in an industrial population - Jaafar, N.; Razak, I.A.; Zain, R.B. (1989)
The aim of this study is to determine the social impact of oral and facial pain in a sample involving an industrial population. Out of a total of 355 subjects interviewed, nearly one-half claimed to have oral and facial pain in the previous one month prior to the survey. The most common type of pain was that related to hot or cold fluids or sweet things followed by toothache. On the average, the pain lasted for 4.2 days (SD = 4.9) per person in the past one-month. About one in five persons with pain reported that it was severe enough to disrupt sleep. About one in ten persons reporting pain had to take sick leave because of the pain. However, only one in four persons with pain consulted a doctor or dentist. More than one-third tried to cope with the pain and did nothing while the rest tried various means of self-cure. It is therefore postulated that in this population, pain per se is a poor predictor of utilisation of dental services. Further research into pain coping behaviour and how this affects of pattern of utilisation of dental services is indicated in order to formulate a strategy to encourage the habit of seeking prompt dental care by the target population.